Estudos da interação da enzima InhA (EC 1.3.1.9) de Mycobacterium tuberculosis H37Rv com análogos do inibidor IQG607 - Cohen, Elisângela Machado Leal (2013)
Since its discovery, Isoniazid remains the main drug used to treat tuberculosis, which has the 2-trans-enoyl-ACP(CoA) reductase or InhA enzyme of Mycobacterium tuberculosis as pharmacological target. However, the increase in cases of tuberculosis resistant to Isoniazid motivated the pharmaceutical industry and research groups to investigate possible inhibitors to InhA, whether seeking for new compounds that display the inhibitory function, or as proposed in this work, modifying existing compounds. Thus, we believe that the IQG607 inorganic compound, also known as pentacyano(Isoniazid)ferrate (II) - developed in an attempt to find new, more potent and selective inhibitors of the InhA enzyme - is a promising candidate for the development of new anti-tuberculosis drugs. This work began with a literature review in order to understand the role of InhA enzyme in the process of fatty acid synthesis and what they represent in the process of formation of the cell envelope of mycobacteria. In addition, a survey was conducted regarding the published studies on the IQG607, which reported efforts engaged in researching and obtaining the compound. Based on these studies, it was proposed the design of new compounds by introducing structural modifications in the IQG607 molecule, with the aid of specific software. Intermolecular interactions of these compounds with the target protein were simulated and evaluated with the use of AutoDock and LigPlot. Twenty-seven models were designed, and for all of them, simulations were performed in silico. Three of these compounds were selected, and from those one was successfully synthesized. After synthesis, enzymatic assays were carried out to assess whether the new compound haddemonstrated inhibitory function as found in the original IQG607. Unfortunately, although the in silico simulations have led us to believe that the models designed could generate good compounds, early in the in vitro experiments we found that there was no variation in the enzyme s activity, indicating that the compound showed no inhibitor effect. In our attempt to lengthen the IQG607 compound - thus allowing a greater number of torsion angles for the molecule, and thereby promote a better fit of the ligand binding cavity in the substrate - we discovered that two important pieces of INH were separated, which caused the loss of activity of the compound. It appears that the changes which were introduced in the IQG607 compound have hindered the acyl radical formation and therefore the adduct ligand-NADH could not be formed.